Peculiarities of expression of HIF-1Α and HIF-3Α in hypothalamus of Wistar rats under the influence of intermittent hypobaric hypoxia - A. V. Abramov; V. A. Shamenko (Patologìâ)
The purpose of this study was to establish the features of the expression of hif‑1α and hif-3α genes and the accumulation of HIF-1α and HIF-3α proteins in the paraventricular (PVH) and supraoptic (SO) nuclei of the hypothalamus under the conditions of intermittent hypoxia and in post-hypoxic periods.